External debt : definition, statistical coverage and methodology - The Bank for International Settlements (Paris : The Bank for International Settlements, 1988)
The book is a progress report on what the International Group on External Debt Statistics has achieved in providing user of debt statistics a comparative description of statistics collected by them, how they are obtained, why they take the form they do and how they relate to each other.
A report by an international working group on external debt statistics of : the World Bank; International Monetary Fund; Bank for International Settlements; and Organisation for Economic Co-operation and Development.
Includes bibliographical references: p. 176-178.
gp 22/01/2109
Loans
Keywords: External debt; United States